PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI SMP NEGERI 3 PADANGSIDIMPUAN - Rini Agustini (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: The problem that is often faced by teachers when the learning process takes place is finding students who are not enthusiastic in attending the lesson. Teachers are always required to be able to motivate students, because in learning there is a need for motivation. The more precise the motivation given, the more successful the lesson will be for students. One of the Islamic education tools that can motivate students to learn is reward and punishment. So, the reward and punishment can be done by the teacher to increase student motivation so that they get good achievements. The problem is whether there is a significant effect of reward and punishment on the motivation to learn students' Islamic education simultaneously at Padangsidimpuan 3 Public Middle School? The purpose of this study was to determine whether there was a significant effect of reward and punishment on the learning motivation of students' Islamic Education simultaneously in Padangsidimpuan 3 Public Middle School. The results of this study there is a significant effect of reward on student learning motivation of 0.715, its contribution is 51.1225%, the remaining 48.8775% is determined by other variables. This gives a statement that the reward has a strong influence on student learning motivation. The magnitude of the effect of punishment on student learning motivation is 0.567, its contribution is 32.1489%, the remaining 67.85% is determined by other variables. This gives a statement that punishment has a strong enough influence on student learning motivation. The magnitude of the effect of reward and punishment is 0.734, its contribution is 53.8756%, the remaining 46.124% is determined by other variables. It provides information that reward and punishment simultaneously have a strong influence on student learning motivation. Keywords: Reward, punishment, and learning motivation.